Integrasi Pendidikan Islam Dalam Pengelolaan Kelas Untuk Pembentukan Generasi Berkarakter - Agustin, Maulid; Nuha, Nazahah Ulin (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2024)
This research discusses the importance of integrating Islamic education in classroom management to shape student character and improve academic achievement. Although there are barriers such as a lack of teacher training and government support, recommended solutions include providing comprehensive training, integrating Islamic education with other sciences, emphasizing individual differences, providing specific instructional instructions, applying the lesson study approach and encouraging the integration of Islamic values in all aspects of education. The research method used was a literature study and qualitative data analysis to identify challenges and solutions in the integration of Islamic education in classroom management. The results show that the integration of Islamic education in classroom management is seen to improve student character, academic achievement and the overall learning experience. By focusing on holistic student character building, values such as sincerity, simplicity, independence, tolerance and care for the environment can be instilled. The role of teachers in instilling character values in students through their example and guidance is crucial. Evaluating students' characters and overcoming obstacles in the integration of Islamic education is also an important part of achieving the broader goals of education, particularly in shaping a young generation that has strong characters and good morals.